2015
DOI: 10.1186/s12935-015-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 predicts disease-free survival in breast cancer

Abstract: BackgroundCyclin D3, which induces progression through the G1 phase of the cell cycle, is a regulator of Cyclin-dependent kinases 4 and 6. Previous studies revealed that abnormal expression of Cyclin D3 was found in many different cancers. However, the role of Cyclin D3 in breast cancer (BC) remains unknown. The aim of this study is to examine the expression pattern of Cyclin D3 in BC and to evaluate its biological role and clinical significance in prognosis prediction. The mechanism involved is also evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…The search result yielded 543 studies from PubMed, EMBASE, and Web of Science. Based on the inclusion and exclusion criteria, a total of 14 studies were selected for our meta‐analysis for a further evaluation . The flow chart of the literature search and screening process were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search result yielded 543 studies from PubMed, EMBASE, and Web of Science. Based on the inclusion and exclusion criteria, a total of 14 studies were selected for our meta‐analysis for a further evaluation . The flow chart of the literature search and screening process were shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…miR‐195 targets cyclin D3 to cause cell cycle arrest at the G1 phase, resulting in the reduction of NSCLC cell growth . Furthermore, Chi et al reported that cyclin D3 could serve as an independent prognosis marker in breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…CCND3-encoding protein cyclin D3 is an important regulator in the progression through the G0/G1 phase of cell cycle 18. Downregulation of cyclin D3 contributes to induction of cell cycle arrest in a variety of cancer cells 19 20.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Hai‐hao Wang revealed that overexpression of miR‐212‐5p significantly suppressed the expression of the CCND3 protein by targeting the CCND3 gene and that upregulation of CCND3 positively correlated with cell growth in miR‐212‐5p overexpressing adult T‐cell leukaemia/lymphoma cells, which was accompanied by restoration of cell cycle progression and reduction of apoptotic death . It was also reported that CCND3, encoding protein cyclin D3, played an important role in controlling the advancement through the G0/G1 phase of the cell cycle . XIAP, a key molecule of the cell apoptosis pathway, could prohibit cell apoptosis by inhibiting caspase‐3, caspase‐7 and caspase‐9 .…”
Section: The Role Of Mir‐212 In Cancermentioning
confidence: 98%
“…25 It was also reported that CCND3, encoding protein cyclin D3, played an important role in controlling the advancement through the G0/G1 phase of the cell cycle. 26 XIAP, a key molecule of the cell apoptosis pathway, could prohibit cell apoptosis by inhibiting caspase-3, caspase-7 and caspase-9. [27][28][29] In renal cell carcinoma (RCC), it was found that miR-…”
Section: Mir-212 and Cell Apoptosismentioning
confidence: 99%